Accumulation of mercury in sediment and bivalves from Cua Dai estuary, Hoi An city - Khanh, Nguyen Van; Minh, Vo Van; Vinh, Nguyen Duy; Hai, Luu Duc (VNU Journal of Science: Earth and Environmental Sciences; Vol 26 No 1, 2010)
Abstract. The paper presents the research results of accumulation of Mercury in sediment and two bivalves species: Heamolymph Clam ( Meretrix meretrix ) and Clam ( Corbicula sp .) from Cua Dai estuary, Hoi An city. The average concentration of Hg in sediments is 0.145 ± 0.052 μg/g, under allowed limit by the PELS standard (Canada) (≤ 0.7 μg/g). Content of Hg accumulated in the tissues of Meretrix meretrix is 0.073 ± 0.045 μg/g and H is 0.066 ± 0.044 μg/g, lower than the allowed standard of the Ministry of Health. Concentration of Hg in sediments and tissues of Meretrix meretrix is positive correlation, at "medium correlation” (r = 0.311, Pvalue = 0.415), while for Corbicula sp. is lower correlation, with "weak correlation” (r = 0.138, Pvalue = 0.722). Results show that, at Cua Dai estuary (city of Hoi An), Meretrix meretrix can be used as bio-indicator species for Hg pollution. Keywords: toxicity, pollution, accumulation, bioindicator, Meretrix, Corbicula.